Therapy considerations for getting athletes to return to play - Fedorczyk, J. M. (Clinics in Sports Medicine, 2020)
During the protective phase of treatment, therapy for hand and wrist injuries in athletes is similar to the plan of care provided to all patients. The nuances in the care provided to athletes become apparent during the transition to the postprotective phase of rehabilitation when the focus has shifted to return to play. Therapy following a sports injury should address the individual needs of the athletes in their everyday lives as well as the specificity of their training and sports-specific activities. The factors that influence return to play are discussed.